Grain characterization of tropical waxy corn hybrid “Danac waxy 1” (Bioagro, 2018)
Venezuelan corn wet milling industry uses waxy corn in order to obtain modified starches for industrial uses. This corn has special characteristics and its grain is imported from temperate countries where hybrids with high adaptability has been developed. The objective of this study is to characterize the new tropical waxy hybrid “Danac waxy 1” (DWX-1). This is a white grained simple hybrid developed through introduction of the waxy gene from an accession of Danac's germplasm bank in elite white grained normal inbred lines. In order to characterize DWX-1 grain, an experimental plot was established in 2016 at San Javier in Yaracuy, Venezuela. The grain was semi dent, spherical, with decolored pericarp and opaque ivory color endosperm. It shows after dry milling a high endosperm yield (75.1 %) and a high proportion of big sized endosperm particles (≥4.75 mm), averaging 60.1 %. The starch granules are polygonal and spherical, with a reddish pigmentation in contact with lugol solution attributable to low amylose content (1.7 %). Amylographic profile of endosperm flour shows high viscosity and low retrogradation. After cooking, the slurry of water and endosperm is fluid, adhesive and has low consistency. Results demonstrate that DWX-1 has a high technological potential for local production of grain with high value functional starches, reducing the need for importation of the national industry.
Keywords: Amylopectin; amylographic profile; amylose; endosperm starch